Islamic Career Guidance for Academic Procrastination Behavior of Students at Muhammadiyah University Enrekang Class of 2017 - Handayani Sura; Muhammad Junaedi Mahyuddin; Elihami Elihami (Edumaspul: Jurnal Pendidikan, 2024)
Academic procrastination such as tending to postpone assignments and not being able to manage time well so as to delay or complete the assignments given. The aim of the research is to determine student procrastination behavior and service patterns towards these students. Method used namely a qualitative field approach (field research). Data collection techniques are through interviews and observation. The results of the research show that the academic procrastination behavior found was: Being late for class, postponing carrying out assignments given by the lecturer in charge of the course, carrying out other activities and permission to study in class, attendance not being optimal, and also being too engrossed in the organizational world so that it is threatened DO. Then to the procrastination is provided with Islamic career guidance services which include recognizing one's potential. where in each session they are guided to make a live proposal. The live proposal will determine when, where and how the career will be achieved. Then doing Affirmations is intended to help students create positive sentences written in "life proposals". The positive sentences are in the form of encouraging sentences. The sentences are short so they are easy and easy to remember. Like I learn from every experience and become wiser every day. I am a source of inspiration for my peers. I deserve to be happy with a more meaningful life, according to the instructions of the Al-Qur'an and Hadith.